2018
DOI: 10.1002/mnfr.201800189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of miR‐140 Deficiency on Non‐Alcoholic Fatty Liver Disease

Abstract: Scope: We have previously shown that loss of miR-140 has a pro-fibrotic effect in the mammary gland. This study aims to investigate whether miR-140 loss and obesity act synergistically to promote non-alcoholic fatty liver disease (NAFLD), and to identify the underlying mechanisms. Methods and Results: Liver tissues were isolated from lean-fat-diet and high-fat-diet fed wild-type and miR-140 knockout mice. Using molecular staining and immunohistochemistry techniques, increased development of NAFLD and fibroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…miR-140-3p has a pro-fibrosis effect. It has been demonstrated that miR-140-3p has a pro-fibrotic effect in the mammary gland14 and is deeply involved in liver disorders,131516 including hepatic impact injury, non-alcoholic fatty liver disease, and hepatocellular carcinoma. Progressive liver fibrosis is observed in the late stages of various chronic liver diseases, and miR-140 has been predicted to be upregulated in rat HSCs during activation 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-140-3p has a pro-fibrosis effect. It has been demonstrated that miR-140-3p has a pro-fibrotic effect in the mammary gland14 and is deeply involved in liver disorders,131516 including hepatic impact injury, non-alcoholic fatty liver disease, and hepatocellular carcinoma. Progressive liver fibrosis is observed in the late stages of various chronic liver diseases, and miR-140 has been predicted to be upregulated in rat HSCs during activation 12.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing expression thereof during the development of fibrosis of the liver and progressive liver fibrosis have been posited in the late stages of various chronic liver diseases. Research has demonstrated that miR-140-3p has a pro-fibrotic effect in the mammary glands14 and is deeply involved in liver disorders,121516 including hepatic impact injury, non-alcoholic fatty liver disease, and hepatocellular carcinoma. Thus, we planned to investigate the role of miR-140-3p in HSC activation and its molecular signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have crucial roles in many cellular processes, as well as in varieties of diseases, including cancers and metabolism-related disorders [ 25 28 ]. A great number of dysregulated miRNAs have been reported in NAFLD, such as miR-21, miR-140 [ 16 , 29 ]. miR-206 has been shown to play key roles in development, cell proliferation, and differentiation [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these miRNAs have been demonstrated to be associated with pathological outcomes in a number of other hepatocyte models including those modeling HCC. ( 10,37‐47 )…”
Section: Discussionmentioning
confidence: 99%